1995
DOI: 10.1182/blood.v86.7.2516.bloodjournal8672516
|View full text |Cite
|
Sign up to set email alerts
|

The Mpl-ligand or thrombopoietin or megakaryocyte growth and differentiative factor has both direct proliferative and differentiative activities on human megakaryocyte progenitors

Abstract: Previously, it was believed that megakaryocytopoiesis was regulated by two types of humoral factors: megakaryocyte colony-stimulating factor (MK-CSF), which acts on progenitors inducing their proliferation, and thrombopoietin (TPO), a megakaryocyte(s) (MK) maturational factor that induces platelet formation. The recently cloned Mpl-ligand (Mpl-L) seems to have both properties in vivo and in vitro and has also been called TPO. However, it cannot be excluded that a part of these activities is due to a synergisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
62
0
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 0 publications
6
62
0
3
Order By: Relevance
“…It could be argued that these differences could be a consequence of the experimental conditions, as only TPO was added to the culture medium. However, TPO alone is able to support in vitro maturation of megakaryocytes (Debili et al, 1995;Dolzhanskiy et al, 1997). Additionally, similar differences in ploidy levels have been observed in megakaryocytes cultured in various culture conditions from a range of fetal and adult sources (Vitrat et al, 1998b;Ma et al, 2000;Miyazaki et al, 2000).…”
Section: Discussionmentioning
confidence: 66%
“…It could be argued that these differences could be a consequence of the experimental conditions, as only TPO was added to the culture medium. However, TPO alone is able to support in vitro maturation of megakaryocytes (Debili et al, 1995;Dolzhanskiy et al, 1997). Additionally, similar differences in ploidy levels have been observed in megakaryocytes cultured in various culture conditions from a range of fetal and adult sources (Vitrat et al, 1998b;Ma et al, 2000;Miyazaki et al, 2000).…”
Section: Discussionmentioning
confidence: 66%
“…This observation is concordant with previously published studies using cord blood progenitors (Schipper et al, 1998), but it differs from the results obtained by Nishihira et al (1996), who found that the optimal rTpo concentration was 50 ng/ml, and Murray et al (1998), who showed increasing numbers of colonies with rTpo concentrations as high as 100 ng/ml. Similarly, studies using progenitor cells from adults have described maximal colony growth using concentrations of rTpo as varied as 1 ng/ml (Teramura et al, 1997), 5 ng/ml (Debili et al, 1995) and 100 ng/ml (Angchaisuksiri et al, 1996). These differences are probably related to the different culture systems used, the presence of serum or serumderived products in the cultures (which might contain factors that affect MK colony growth) or the type of cells plated (unfractionated marrow cells, peripheral blood progenitors, CD34 1 cells, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Thrombopoietin (Tpo) is the main regulator of platelet production (Kaushansky, 1995) and, therefore, is a probable candidate to play a role in the platelet rise. Tpo alone can stimulate both proliferation and differentiation of megakaryocytic cells, which eventually results in the release of platelets in the circulation (Wendling et al, 1994;Choi et al, 1995;Debili et al, 1995a;Kaushansky et al, 1995;Cramer et al, 1997;Gehling et al, 1997;Norol et al, 1998). A potential increase in circulating Tpo after major surgery may arise via different mechanisms.…”
mentioning
confidence: 99%